Evidence Base Update of Psychosocial Treatments for Pediatric Obsessive-Compulsive Disorder: Evaluating, Improving, and Transporting What Works. Issue 5 (3rd September 2018) - Freeman, Jennifer; Benito, Kristen; Herren, Jennifer; Kemp, Joshua; Sung, Jenna; Georgiadis, Christopher; Arora, Aishvarya; Walther, Michael; Garcia, Abbe
Abstract : Pediatric obsessive-compulsive disorder is a chronic and impairing condition that often persists into adulthood. This review refreshes the state of support for psychosocial treatments and the predictors or moderators that relate to their efficacy and evaluates how the literature has improved since the last update in 2014. A secondary goal is to propose an additional framework for the categorization of studies based on central research questions rather than treatment format. Psychosocial treatment studies conducted since the last review are described and evaluated according to methodological rigor and evidence-based classification using the Journal of Clinical Child and Adolescent Psychology evidence-based treatment evaluation criteria. Findings again converge in support of cognitive-behavioral therapy (CBT) as an effective and appropriate first-line treatment for youth with obsessive-compulsive disorder. Family-focused CBT is now well-established . A number of other treatments including CBT+ D-Cycloserine, CBT+ Sertraline, CBT+ positive family interaction therapy, and technology-based CBT are now probably efficacious . Demographic, clinical, and family factors are consistent predictors of CBT outcome with conflicting findings for neurocognitive predictors. The field has advanced significantly since the last review, but there is still room for improvement. Some of the conclusions that can be drawn may be limited by our evaluation criteria. Future directions are proposed to advance treatment outcome research beyond a focus on which treatments work to exploring factors that account for how and why they work.